2021
DOI: 10.3389/fimmu.2021.628168
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Deficiency Protects Against Intermittent Hypoxia-Induced Neuroinflammation and Mitochondrial ROS by Promoting the PINK1-Parkin Pathway of Mitophagy in a Murine Model of Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) associated neurocognitive impairment is mainly caused by chronic intermittent hypoxia (CIH)-triggered neuroinflammation and oxidative stress. Previous study has demonstrated that mitochondrial reactive oxygen species (mtROS) was pivotal for hypoxia-related tissue injury. As a cytosolic multiprotein complex that participates in various inflammatory and neurodegenerative diseases, NLRP3 inflammasome could be activated by mtROS and thereby affected by the mitochondria-selective autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…In accordance, it has been shown that obese subjects with OSAS have increased levels of leptin and higher NLRP3 activity [121,122]. Conversely, NLRP3 deficiency protected against IH in a mouse model of OSAS [123]. Taken together, these findings suggest a vicious circle where obesity favours OSAS and IH promotes adipose tissue inflammation.…”
Section: Impairment Of the Nlrp3 Inflammasome In Obesity Leads To Pul...supporting
confidence: 59%
“…In accordance, it has been shown that obese subjects with OSAS have increased levels of leptin and higher NLRP3 activity [121,122]. Conversely, NLRP3 deficiency protected against IH in a mouse model of OSAS [123]. Taken together, these findings suggest a vicious circle where obesity favours OSAS and IH promotes adipose tissue inflammation.…”
Section: Impairment Of the Nlrp3 Inflammasome In Obesity Leads To Pul...supporting
confidence: 59%
“…Furthermore, enhancement of mitophagy can prevent iodinated contrast-induced RTEC injury [ 14 ]. Several studies confirmed the protective role of mitophagy in IH-induced organ impairment [ 21 23 ]. A study revealed that NLRP3 deficiency, which enhanced Parkin-mediated mitophagy, played a protective role in IH-induced neuroinflammation [ 21 ].…”
Section: Discussionmentioning
confidence: 92%
“…Research pointed 99 that NLRP3 deficiency can reduce oxidative stress and scavenge damaged mitochondria, and it seems to play an important role in neuroinflammation. After activation of NLRP3 inflammasome, the release of IL-1 β, IL-18 and other inflammatory factors will activate the polymorphonuclear neutrophils, produce a large number of ROS, and initiate the inflammatory response.…”
Section: Relation Of Nlrp3 and Oxidative Stressmentioning
confidence: 99%